STRATEGI QATAR DALAM MENGHADAPI EMBARGO EKONOMI NEGARA-NEGARA TELUK (ARAB SAUDI, UNI EMIRAT ARAB DAN BAHRAIN) TAHUN 2017-2018 - Gustantia, Yola; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is aimed to explain some of the strategies applied by Qatar government in battling the economic embargo from gulf nation in 2017-2018. In 5th of june 2017, several of gulf nation such as Saudi Arabia, UAE, and Bahrain severed diplomatic alliance and enforce embargo towards Qatar by blocking land, water, and air trade routes towards Qatar. The embargo affected the economic sector of Qatar. This embargo is motivated due to the accusations of terrorist involvement in Qatar from Saudi Arabia that can threaten the security and internal affairs of several other countries.This research uses the theory of national interest from Donald E Nuechterlein which is divided into four basic interests of the country including Defense of Homeland, Economic Well-being, Favorable World Order and Promotion of Values. In the case of Qatar's economic embargo, two out of four basic interests are used which were Defense of homeland, and Economic well-being. The level of this analysis is Mochtar Mas'oed's Nation-State withqualitative research methods are descriptive explanatory. This research shows, the strategies that is being used by Qatar in facing the economic embargo is by arranging military agreement with Turkey, establishing a new trade routes between Turkey and Qatar through Iran, e-commerce arrangement between Turkey and Qatar, using Iran airspace for all ongoing flight routes by Qatar, establishing sea routes for trade between Qatar and Oman, and increasing invesment and trades between Oman and Qatar. Keywords: strategy, diplomatic inf